Cantonese advantage on English stress perception: Constraints and neural underpinnings. (30th July 2021) - Choi, William
Abstract: A prevailing conception of cross-linguistic transfer is that first language experience poses perceptual interference, or at best null effect, on second language speech perception. Surprisingly, a recent study found that Cantonese listeners outperformed English listeners on English stress perception. The present study further evaluated whether segmental variations would constrain the Cantonese advantage on English stress perception. Cantonese and English listeners were tested with both active and passive oddball paradigms in which ERP responses to English stress deviations were elicited. Behaviorally, the Cantonese listeners exhibited a perceptual advantage relative to the English listeners, but this advantage disappeared upon the introduction of segmental variations. Neurophysiologically, segmental variations diminished the P3b amplitudes of the Cantonese but not the English listeners. Collectively, results suggest that segmental variations constrain the Cantonese advantage on English stress perception. Highlights: Cantonese listeners outperform English listeners on English stress perception. The Cantonese advantage is constrained by segmental variations. The segmental constraint manifested neurophysiologically as reduced P3b amplitudes.